A consanguinidade como impedimento aos casamentos em Minas Gerais : entre a tradição familiar e os estudos genéticos - Gabriel Afonso Vieira Chagas (2024)
This thesis was motivated by the observation of the change in marital behavior of some family groups at the turn of the 19th to the 20th century. Among these, the Ferreira da Fonseca family stands out, which once systematically used consanguineous marriages to preserve the territorial extension of the Olhos D’Água farm over the course of a century and a half. This group reached a high rate of 83.33% of intra-family marriages in the fifth generation after establishment in Brazil, which covers the period 1864-1890. At the same time that the debate about the condemnation of family marital endogamy was intensifying in the Brazilian medical profession, a dizzying drop in the rate of consanguinity in marriages was observed in this family. In just two generations, consanguineous marriages came to represent just 22.85% of the total number of unions – this in the period from 1923 to 1958. A similar movement was observed in the Ferreira Armond and Rodrigues Chaves families, both involved in commerce in the province. For this reason, this work focused on the adherence of a group of Brazilian doctors from the 19th century to the self-styled anti-consanguinist school, which advocates that the consanguineous marriage of parents had potentiating effects on the generation of offspring carrying heredity diseases. The aim is to suggest a relationship between the dissemination of these studies and the marriage decisions of family groups that gradually abandoned the practices of consanguineous marriages, giving way to extra-family marriages. Thus, aware of the multiplicity of factors that generated the change in the marital behavior of those who began to discredit consanguineous marriages, this thesis focuses only on the construction of the medical discourse that blamed family endogamy for the recurrence of a wide range of hereditary anomalies without delving into other reasons for the decrease in this practice, even repeatedly indicating the awareness of their existence and action. With this, the objective is to contribute to studies in the field of History of Science, focusing on the appropriation and dissemination of the European discourse about hereditary diseases and impediments to consanguineous marriages by a considerable range of Brazilian doctors. The analysis of articles present in Brazilian medical journals from the 19th century, combined with theses written by Minas Gerais doctors trained at the Faculdade de Medicina do Rio de Janeiro and preserved in the Arquivo Público Mineiro, allows us to reconstruct the access and forms of dissemination of medical research. international scientific studies that concern theories about the role of heredity in the transmission of consanguineous diseases under the agenda of the Brazilian medical profession. Furthermore, these texts are a privileged thermometer to measure the existence and scope of this debate among Brazilian doctors or those based in the country. Thus, the drop in consanguineous marriage rates at the end of the 19th century is taken as an indication that, among other factors, this discourse had a significant impact on changing the marriage strategies of these family groups.